The identity reflection of code-switching in How to tame a wild tongue - Barboza, Mariana Gomes (2024)
This work presents bibliographical research that analyzes code-switching in the chapter titled How to Tame a Wild Tongue from Gloria Anzaldúa’s Borderlands/La Frontera: The New Mestiza. The study investigates the relationship between code-switching and the principle of identity reflection and explores the different types of code-switching used in the text. Through a combination of qualitative and quantitative approaches, the research draws upon the theoretical perspectives of Poplack (1980) and Lo (2007). Moreover, data acquisition involved analyzing excerpts from the chapter and comparing them with the categories under study. The results suggest that Anzaldúa used code-switching to demonstrate her identity and connection to multiple languages. She used this technique to reflect her complex linguistic and cultural background. --- Original in English.